An Analysis of Proper Vibrations of the Missile Launcher - Motor Vehicle Assembly Using the Main Coordinates - Zbigniew DZIOPA; Maciej NYCKOWSKI (Problemy Mechatroniki)
The study examined an assembly composed of a motor vehicle with a launcher of unguided missiles mounted on it. A real self-propelled missile assembly was used to develop a physical model, and then Lagrange equations of the second type were applied in order to implement a mathematical model. The characteristic values and eigenvectors were determined on the basis of the equations describing the autonomous and conservative motion of the system. The main coordinates were introduced and the orthogonality conditions of the proper vibrations forms were checked with the designated dynamic characteristics of the analyzed system. Then the independent equations of vibrations of the missile launcher-motor vehicle assembly were determined taking into consideration the characteristic values and eigenvectors. To conclude, an analysis of vibrations of the considered system was conducted.